Characteristics and Mechanism Analysis of Aerodynamic Noise Sources for High-Speed Train in Tunnel - Xiao-Ming Tan; Hui-fang Liu; Zhi-Gang Yang; Jie Zhang; Zhong-gang Wang; Yu-wei Wu (Complexity)
We aim to study the characteristics and mechanism of the aerodynamic noise sources for a high-speed train in a tunnel at the speeds of 50 m/s, 70 m/s, 83 m/s, and 97 m/s by means of the numerical wind tunnel model and the nonreflective boundary condition. First, the large eddy simulation model was used to simulate the fluctuating flow field around a 1/8 scale model of a high-speed train that consists of three connected vehicles with bogies in the tunnel. Next, the spectral characteristics of the aerodynamic noise source for the high-speed train were obtained by performing a Fourier transform on the fluctuating pressure. Finally, the mechanism of the aerodynamic noise was studied using the sound theory of cavity flow and the flow field structure. The results show that the spectrum pattern of the sound source energy presented broadband and multipeak characteristics for the high-speed train. The dominant distribution frequency range is from 100 Hz to 4 kHz for the high-speed train, accounting for approximately 95.1% of the total sound source energy. The peak frequencies are 400 Hz and 800 Hz. The sound source energy at 400 Hz and 800 Hz is primarily from the bogie cavities. The spectrum pattern of the sound source energy has frequency similarity for the bottom structure of the streamlined part of the head vehicle. The induced mode of the sound source energy is probably the dynamic oscillation mode of the cavity and the resonant oscillation mode of the cavity for the under-car structure at 400 Hz and 800 Hz, respectively. The numerical computation model was checked by the wind tunnel test results.